Inovação de produto sob a perspectiva da visão baseada em recurs - Back, Greice Daniela (My University, 2016)
Based on the relevance of studies of innovation as an element that contributes to economic development and the theory of Resource Based View, which presents the strategic resources of the firm as a source for competitive advantage, this paper aims to investigate the innovations in products from the perspective of Resource Based View, specifically in Rio Grande do Sul microbreweries. The selected method was the exploratory and descriptive qualitative research with case study strategy and data collection method through semistructured interviews, applied to microbreweries managers that had recognition of their products in national and international awards. Data analysis was done through the interpretation of interview transcripts. The categorization was previously established to answer the three specific objectives proposed: identify the product innovations in Rio Grande do Sul microbreweries; identify the resources explored by microbreweries that generate innovation; and identify the resources that have the potential to generate sustainable competitive advantage. As a result, it was possible to identify the product innovations in packaging, bottling and quantity when it comes to color, texture, scent and flavor within the styles of the beers produced. It was identified as physical resources in product innovation, geographic location, access to raw materials, the industrial structure and the brewing lab. Human resources appear in the development process of new products in the form of experience exchange between employees and partners, technical courses and the experience exchange with brew masters and other partner employees companies, including other microbreweries. As organizational resources identified are relationship between company groups with the external environment. As for financial resources stands out planning on the acquisition of physical resource, especially for the purchase of raw material, as a facilitator of innovation. The resources that have gone through VRIO model and that generate innovation in product with imperfectly imitable features mentioned by respondents are the organizational and human resources. The action of interaction between the microbreweries is based on tacit knowledge and occurs informally. The characteristic of the identified organizational resources uses the strategy to create new products that can generate sustainable competitive advantage, based on an open innovation and reputation of the product ahead to distribution channels.
Com base na relevância dos estudos da inovação como elemento que contribui para o desenvolvimento econômico e na teoria da Visão Baseada em Recursos, que apresenta os recursos estratégicos da firma como uma fonte para obter vantagens competitivas, este trabalho tem como objetivo principal investigar as inovações em produtos pela perspectiva da Visão Baseada em Recursos, especificamente nas microcervejarias do Rio Grande do Sul. O método selecionado foi a pesquisa qualitativa exploratória e descritiva com estratégia de estudo de caso e método de coleta de dados por meio de entrevistas semiestruturadas, aplicada aos gestores das microcervejarias que tiveram o reconhecimento dos seus produtos em premiações nacionais ou internacionais. A análise de dados se deu pela interpretação das transcrições das entrevistas. A categorização foi estabelecida previamente para atender a três objetivos específicos propostos: identificar as inovações em produtos nas microcervejarias do Rio Grande do Sul; identificar os recursos explorados pelas microcervejarias que geram a inovação; e, identificar os recursos que têm potencial para gerar vantagem competitiva sustentável. Como resultado, foi possível identificar as inovações em produtos na embalagem, quantidade de envaze e no que tange a cor, a textura, o aroma e o sabor, dentro dos estilos das cervejas produzidas. Foram identificados como recursos físicos para a inovação em produto a localização geográfica, o acesso à matéria-prima, a estrutura fabril e o laboratório cervejeiro. Os recursos humanos aparecem no processo de desenvolvimento dos novos produtos na forma de troca de experiências entre funcionários e sócios, cursos técnicos e a troca de experiência com mestres cervejeiros e demais colaboradores de empresas parceiras, incluindo outras microcervejarias. Como recursos organizacionais identificados estão a relação entre grupos da firma com o ambiente externo. Quanto aos recursos financeiros destaca-se o planejamento ligado à aquisição de recurso físico, em especial para a compra de matéria-prima, como facilitador da inovação. Os recursos que passaram pelo modelo VRIO e que geram a inovação em produto com características imperfeitamente imitáveis apontados pelos entrevistados são os recursos organizacionais e humanos. A ação de interação entre as microcervejarias é baseada em conhecimentos tácitos e ocorre de forma informal. A característica dos recursos organizacionais identificados usa a estratégia para a criação de novos produtos que podem gerar vantagem competitiva sustentável, apoiada nas redes de inovação e na reputação do produto frente aos canais de distribuição.
Keywords: Administração de produtos; Produtos novos; Empreendedorismo; Desenvolvimento organizacional; Planejamento empresarial; Product management; New products; Entrepreneurship; Organizational change; Business planning